The Fast and Accurate Method of Tuning of SISO Controllers Using Seven Performance Indexes - Stopakevych A.О.; Stopakevych О.A. (Problems of the Regional Energetics)
The goal of the work is the development of an algorithm and corresponding software, which allows the execution of multi-criteria optimization of a control system with PI controller and FOPDT plant. We use the following seven performance indicators to find the optimal tunings: gain margin, phase margin, cutoff frequency, critical frequency, relative delay margin, relative overshoot, maximum control action magnitude. Optimization criteria can include constraints on any number of indicators. The goal of the work has been achieved by solving the following tasks. The first task is to create formulas and procedures for accurate calculation of performance indicators of control systems. The second task is to develop a procedure for the fastest possible simulation of a control system with the orientation on using a model with internal delays structure and a special solver for it. The third task is to develop an algorithm for fast calculation of performance indicators in the range of all possible rational tuning of the controller for a given FOPDT plant model. The fourth task is to develop a software application with a graphical interface in MATLAB language, which allows convenient optimization for an arbitrary rational FOPDT model. The most significant result was that the pointed-out performance indicators can be accurately calculated for all possible rational tunings of a PI controller with an arbitrary FOPDT model in a second. The significance of the results was that it allows to reduce an optimization procedure to a table search and to achieve any multi-term performance criteria. The effectiveness of the procedure has been demonstrated on a set of different FOPDT models. It is shown that there is no dependence in accuracy of calculation from model or controller coefficients.